Early retirement as a privilege for the rich? A comparative analysis of Germany and Switzerland - Ursina Kuhn; Markus M. Grabka; Christian Suter (Advances in Life Course Research, 2021)
This contribution analyses early retirement in Germany and Switzerland with a focus on financial resources. Using data from CH-SILC linked to administrative records and the German SOEP, we distinguish three different financial resources: namely, pre-retirement labour income, net worth and pension entitlements. High labour income reduces the probability for early retirement. In contrast, high pension entitlements are associated with early retirement. Private wealth also plays an important role in early retirement, but differs with regard to the relevance of the asset components between the two countries. Although the pension system moderates the influence of financial resources on retirement behaviour, the direction of the effects is consistent across the countries once pension entitlements are accounted for.
Keywords: 330; Early retirement; Pension entitlements; Net worth; Income; SOEP; CH-SILC